Delayed parenthood on the rise: A call for upstream preconception health promotion in Canada - Mill, Catriona (Can J Public Health, 2016)
The trend toward delayed parenthood is on the rise across Canada. Societal emphasis on attaining higher education, career advancement and financial security may be some reasons why individuals delay becoming a parent; whatever the reason, this trend is linked to significant health and economic impacts. Many Canadians are unaware of the impact this may have on their fertility and potential birth outcomes. It is important that health care professionals apprise individuals in their reproductive years about these issues and the steps they can take to mitigate these risks. Implementing a health equity and broader determinants of health approach through social policy development may also prove beneficial. Such upstream approaches could enhance maternal and child health outcomes, and also help ensure that people of reproductive age are making an informed decision about delaying parenthood. This article calls for developing a comprehensive preconception health promotion and care strategy encompassing individual, community and population level approaches.